Strengthening Community Service Collaboration Through Basic Life Support (BLS) Training - Dudut Tanjung; Lutfi Henderlan Harahap; Syahferi Anwar; Ismayadi Ismayadi; Yusuf Hanafiah; Athira Demitri; Balqis Nurmauli Damanik; Murni Noviani (International Journal of Health and Medicine, 2024)
The community service project aims to enhance public knowledge and skills in providing immediate assistance during cardiac emergencies. Conducted in collaboration with the Indonesian Emergency and Disaster Nurses Association (HIPGABI) North Sumatra and the Regional Crisis Center Team North Sumatra, this program focuses on training participants in the fundamental techniques of Basic Life Support (BLS), including cardiopulmonary resuscitation (CPR) and the use of automated external defibrillators (AEDs). The training is specifically designed for the congregation of HKBP Resort Kwala Bekala Church. The involvement of HIPGABI North Sumatra and the Regional Crisis Center Team North Sumatra brings expertise and professionalism, ensuring that the training adheres to national standards and best practices in emergency response. The outcomes of this training are expected to strengthen community resilience and preparedness in dealing with health emergencies in Medan and the surrounding areas.